rRNA gene activity and control of expression mediated by methylation and imprinting during embryo development in wheat x rye hybrids - Neves, N. (1995)
Ribosomal RNA genes originating from one parent are often suppressed in interspecific hybrids. We show that treatments during germination with the cytosine analogue 5-azacytidine stably reactivate the expression of the suppressed rRNA genes of rye origin in the wheat x rye amphiploid, triticale, by preventing methylation of sites in the rye rDNA. When 5-azacytidine is applied to embryos of triticale and wheat x rye F1 hybrids nine, or more, days after fertilization, rye rRNA gene expression is stably reactivated in the resulting seedling. Earlier treatments have no effect on rye rRNA gene expression, indicating that undermethylation of DNA early in embryo development is reversible. After 9 days, the methylation status of rRNA genes in maintained throughout development. Since the change in expression follows a methylation change at particular restriction-enzyme sites, the data establish a clear correlation between gene activity and methylation in plants.